(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article discusses the issues of applying modern approaches to teaching biology in various education systems. The study analyzed existing curricula and teaching and learning materials, identified problem areas in the educational process. Specific recommendations are given on optimizing the structure of the biology course, ntroducing innovative pedagogical technologies and methods that serve to provide continuous education and develop students’ scientific thinking.